2007
DOI: 10.1016/j.scitotenv.2007.02.027
|View full text |Cite
|
Sign up to set email alerts
|

Responses of antioxidant defenses to Cu and Zn stress in two aquatic fungi

Abstract: Aquatic hyphomycetes are fungi that play a key role in plant litter decomposition in streams. Even though these fungi occur in metal-polluted streams, the mechanisms underlying their tolerance to metals are poorly documented. We addressed the effects of Zn and Cu in Varicosporium elodeae and Heliscus submersus by examining metal adsorption to cell walls, plasma membrane integrity and production of reactive oxygen species at metal concentrations inhibiting biomass production in 50% or 80%. The activity of the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
69
0
6

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 100 publications
(84 citation statements)
references
References 40 publications
9
69
0
6
Order By: Relevance
“…It was previously demonstrated that the generation of ROS contributes noticeably to copper and zinc toxicity in aquatic hyphomycetes (Azevedo et al, 2007(Azevedo et al, , 2009Pradhan et al, 2015). The interaction of ROS with biological membranes results in a variety of functional alterations due to direct interaction with the molecular cell machinery and/ or oxidative modification of biological macromolecules (Stark, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It was previously demonstrated that the generation of ROS contributes noticeably to copper and zinc toxicity in aquatic hyphomycetes (Azevedo et al, 2007(Azevedo et al, , 2009Pradhan et al, 2015). The interaction of ROS with biological membranes results in a variety of functional alterations due to direct interaction with the molecular cell machinery and/ or oxidative modification of biological macromolecules (Stark, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Specific Cys residues of the H + -ATPase are targets for iron and copper Fenton reagents, leading to enzyme inactivation (Stadler et al, 2003). Consistently, reducedthiol groups were shown to be essential for maintaining H + -ATPase activity under iron stress in wheat root plasma membranes (Yang et al, 2003).We previously reported that exposure of aquatic hyphomycetes to copper and zinc led to intracellular ROS accumulation and plasma membrane disruption (Azevedo et al, 2007). In the hyphomycetes, metal tolerance was associated with increased levels of thiol compounds in cells (Miersch et al, 2001; Braha et al, 2007; Guimarães-Soares et al, 2007), and there is evidence pointing to glutathione, phytochelatins and metallothioneins as putative metal sequesters or ROS scavengers (Jaeckel et al, 2005; Guimarães-Soares et al, 2006).…”
mentioning
confidence: 88%
See 3 more Smart Citations